The Role of BI Rate and Operational Cost to Income of Musyarakah in PT. Indonesia Bank of Muamalat Among 2016-2019 Period - Fitranty Adirestuty (Universitas Pendidikan Indonesia, 2020)
The purpose of this research is to find out how the influence of inflation on revenue sharing results from the musyarakah financing contract, and how the effect of operational costs on revenue sharing results from the musyarakah financing agreement, and how the effect of inflation and operational costs together on revenue sharing from the financing agreement musyarakah at PT. Muamalat Indonesia Bank. This research is a quantitative study. The sample used in this study is in the form of monthly financial reports of PT. Bank Muamalat Indonesia 2016-2019 period published on the official website of Bank Indonesia, the Financial Services Authority, and Bank Muamalat Indonesia by using Purposive Sampling techniques. The type of data used is secondary data. The method used in this research is associative. The analysis model used is the Normality Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Test with a significance level of 5% or 0.05. In this study, to process the data, the author uses the application SPSS 22. The analysis results showed that variables inflation and operational costs partially have a positive and significant effect on revenue sharing from musyarakah financing. Inflation and operational costs affect the revenue-sharing from the musyarakah financing agreement. The Prob value evidences this—statistical 0,000, which is smaller than 0.05. Then the contribution of inflation and operational costs to the revenue of musyarakah financing in this study amounted to 0.419 or (41.9%). At the same time, the remaining 58.9% was explained by other variables not examined or not included in this research model.